SCN1B Gene: A Close Relative to SCN1A - Pasquetti, Elisa; Lo Bianco, Manuela; Sullo, Federica; Patanè, Francesca; Sciuto, Laura; Polizzi, Agata; Praticò, Andrea D.; Zanghì, Antonio; Falsaperla, Raffaele (Journal of Pediatric Neurology, 2021)
One of the first reported genes associated with epilepsy was SCN1B, which encodes for β-subunit of voltage-gated sodium channel of excitable cells and it is critical for neuronal function in both central and peripheral nervous system. β-subunits modulate the expression levels and functional properties of sodium channels and though their immunoglobulin domains may mediate interactions between channels and other proteins. Traditionally, SCN1B mutations were associated with generalized epilepsy with febrile seizures plus, a familial epilepsy syndrome characterized by heterogeneous phenotypes including febrile seizures (FS), febrile seizures plus (FS + ), mild generalized epilepsies, and severe epileptic encephalopathies. Throughout the years, SCN1B mutations have been also associated with Dravet syndrome and, more recently, with developmental and epileptic encephalopathies, expanding the spectrum associated with this gene mutations to more severe phenotypes.
Keywords: SCN1B; SCN1; epilepsy; febrile seizures; GEFS+